Effectiveness of Online Single Submission Policy for Faster Land Transactions Compliance - Raita Varia; Sudiro, Amad; Mella Ismelina F. Rahayu; Tolib Turgun Ugli Rakhmonov (Lembaga Contrarius Indonesia, 2025)
The Job Creation Law, the Online Single Submission–Risk Based Approach, and the Basic Agrarian Law collectively reshape Indonesia’s land licensing system while simultaneously creating substantial regulatory and institutional challenges. This study evaluates the effectiveness of the OSS-RBA policy in accelerating land transaction compliance while preserving legal certainty and administrative efficiency. The research adopts a doctrinal legal method by examining statutory instruments, implementing regulations, and administrative procedures governing land licensing and spatial conformity. To strengthen the analysis, the study integrates a comparative legal approach to assess patterns of institutional coordination and digital governance. The analysis concentrates on three central dimensions: regulatory consistency in land rights verification and spatial suitability, institutional coordination among competent authorities, and the integration of spatial and land information systems. The results show that regulatory overlaps and normative inconsistencies continue to generate legal uncertainty in land licensing. Fragmented institutional authority further weakens coordination and delays administrative decision-making. In addition, limited interoperability between spatial and land databases reduces the effectiveness of digital licensing services. This study concludes that the OSS-RBA policy will effectively accelerate land transaction compliance only through regulatory harmonization, strengthened inter-agency coordination, and the establishment of an integrated spatial–land information system to ensure legal certainty, good governance, and sustainable land administration.